2019
DOI: 10.3390/ijms20236083
|View full text |Cite
|
Sign up to set email alerts
|

Dual RNA Sequencing of Vitis vinifera during Lasiodiplodia theobromae Infection Unveils Host–Pathogen Interactions

Abstract: Lasiodiplodia theobromae is one of the most aggressive agents of the grapevine trunk disease Botryosphaeria dieback. Through a dual RNA-sequencing approach, this study aimed to give a broader perspective on the infection strategy deployed by L. theobromae, while understanding grapevine response. Approximately 0.05% and 90% of the reads were mapped to the genomes of L. theobromae and Vitis vinifera, respectively. Over 2500 genes were significantly differentially expressed in infected plants after 10 dpi, many o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 78 publications
2
22
0
1
Order By: Relevance
“…In addition to PR1 proteins, a large number of genes with antimicrobial properties that encode other PR proteins, including PR2, PR3, PR5, PR9, PR10, and PR14, were mainly up-regulated. This is in accordance with several studies on forest tree-pathogen interaction [ 19 , 27 , 29 , 30 , 32 , 36 , 38 , 40 , 42 , 82 ]. It has been reported that, after F. circinatum infection, JA and SA induce chitinases (PR3) [ 83 ] that degrade chitin, a major component of fungal cell walls.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to PR1 proteins, a large number of genes with antimicrobial properties that encode other PR proteins, including PR2, PR3, PR5, PR9, PR10, and PR14, were mainly up-regulated. This is in accordance with several studies on forest tree-pathogen interaction [ 19 , 27 , 29 , 30 , 32 , 36 , 38 , 40 , 42 , 82 ]. It has been reported that, after F. circinatum infection, JA and SA induce chitinases (PR3) [ 83 ] that degrade chitin, a major component of fungal cell walls.…”
Section: Discussionsupporting
confidence: 93%
“…Además, se debe establecerse una compatibilidad del huésped-patógeno como requisito primario para que se dé una invasión y destrucción del huésped por un agente patógeno, dando como resultado la compatibilidad genética entre enzimas hidrolíticas y los tejidos constitutivos del hospedador (Mabou et al, 2020), esto puede confirmar la capacidad de infección que tienen los morfotipos DH2, DH11, DH20 y DH17 por los tubérculos de ñame espino. Algunos autores sugieren que los cambios ambientales, pueden estimular a que algunos hongos se conviertan en patógenos agresivos, a través de la liberación de enzimas degradantes, proteínas inhibitorias y toxinas (Gonçalves et al, 2019;Perincherry et al, 2020).…”
Section: Discussionunclassified
“…Lasiodiplodia theobromae , a woody plant pathogen belonging to Botryosphaeriaceae family, has received much attention recently for the considerable damage caused by this fungus in fruiter’s industry. Research on this fungus have made great progress during the past two decades including strain isolation, diseases symptoms characterization, enzymatic activity analyses, and genome and transcription analyses ( Cao et al, 2020 ; Félix et al, 2019 ; Gonçalves et al, 2019 ; Paolinelli-Alfonso et al, 2016 ; Úrbez-Torres et al, 2008 ; Yan et al, 2018 ). However, investigation on the pathogenic mechanism are still at a preliminary stage and remain stagnant because of the multinuclear cell structure of this fungus, which seriously constrains the genetic manipulations in molecular studies.…”
Section: Discussionmentioning
confidence: 99%